2017
DOI: 10.1158/1538-7445.am2017-3507
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3507: PVT1 exons 4A, 4B, and 9 are overexpressed in aggressive prostate cancer, and PVT1 exon 4B may distinguish between indolent and aggressive prostate cancer

Abstract: Aggressive prostate cancer (PCa) disproportionately affects males of African ancestry (MoAA). However, the underlying molecular mechanisms are unclear. Chromosome 8q24 is a PCa susceptibility locus that harbors the PVT1 non-coding gene. We previously demonstrated that PVT1 exon 9 may be involved in aggressive PCa. Moreover, using the most recent full-genome variability panel from the 1000 Genomes project, we recently identified a string of 75 SNPs in a 26-kb region spanning PVT1 exons 4A and 4B as consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Further, testing of human prostate tissue samples showed that the number of copies/μl of PVT1 exons 4A, 4B, and 9 is higher in prostate cancer samples in comparison to normal prostate tissues or benign prostatic hyperplasia tissues. These absolute quantitative data agree with the relative expression data we had previously acquired [31], [32]. It is noteworthy that using this novel copy number–based quantification assay, we were able to detect and quantify PVT1 exons 4A, 4B, and 9 in both serum and plasma samples.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Further, testing of human prostate tissue samples showed that the number of copies/μl of PVT1 exons 4A, 4B, and 9 is higher in prostate cancer samples in comparison to normal prostate tissues or benign prostatic hyperplasia tissues. These absolute quantitative data agree with the relative expression data we had previously acquired [31], [32]. It is noteworthy that using this novel copy number–based quantification assay, we were able to detect and quantify PVT1 exons 4A, 4B, and 9 in both serum and plasma samples.…”
Section: Discussionsupporting
confidence: 87%
“…PVT1 is also associated with immune diseases like asthma, vitiligo, and several others [17, 38]. And PVT1 has been demonstrated by multiple studies and research groups to be overexpressed in prostate cancer [32,39]. PVT1 plays an oncogenic role and regulates tumor growth in prostate cancer [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations